Konstruksi Perlindungan Penyandang Disabilitas Mental Dalam Instrumen Hak Asasi Manusia - Handayani, Asri Reni; Maliga, Iga; Sholihah, Nur Arifatus (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Neglected protection for persons with mental disabilities is the result of cultural, social, economic factors, as well as weak law enforcement policies that are pro-disabled. This makes persons with mental disabilities a marginal group who are often victims of abuse, violence, torture and inhumane treatment. The lack of attention to the implementation of the rights of persons with mental disabilities is a big question for the Indonesian government, the government's responsibility should be the implementation of fair legal regulations and the fulfillment of human rights. The rights that must guarantee and recognize the rights of persons with mental disabilities are given in accordance with those regulated by law. This research is normative research. The technique of collecting legal materials is carried out by means of a literature study. The approach used is a statutory approach (statute approach) and a conceptual approach (conceptual approach). This study concludes that protection for persons with mental disabilities has not been implemented optimally. There is still discrimination and negative stigma attached to persons with mental disabilities.